Safety of Routine Pedicle Division during Delayed Breast Augmentation following Free Flap Breast Reconstruction. Issue 6 (June 2021) - Rose, Jessica F.; Doval, Andres F.; Zavlin, Dmitry; Ellsworth, Warren A.; Echo, Anthony; Spiegel, Aldona J.
Abstract : Background: Autologous free flap breast reconstruction is a common reconstructive procedure, with the ability to produce a natural breast shape and a long history of success. Despite its benefits, there are special situations in which patients lack sufficient donor-site tissue to achieve adequate breast size and projection. With this study, the authors describe their institutional experience of delayed implant augmentation after autologous breast reconstruction with a particular focus on pedicle division as a technique to improve aesthetic results. Methods: A retrospective chart review of patients that underwent free flap autologous breast reconstruction with delayed implant augmentation was conducted over a 13-year period. Flaps were divided into a control group without pedicle division and a divided pedicle group. Groups were compared in terms of demographics, clinical and surgical characteristics, implant details, and postoperative implant and flap complications. Results: No significant differences in terms of age, body mass index, comorbidities, radiation therapy, or surgical indications were noted. The most common reason for delayed implant augmentation after autologous breast reconstruction was change in breast size and breast asymmetry. In terms of implant and flap complications, we found no significant differences between the control and divided pedicle groups after delayed implant augmentation. Conclusions: From the authors' institutional experience, pedicle division in delayed breast augmentation with implants after free flap breast reconstruction can be safety performed in selected cases. This technique can be a powerful tool for plastic surgeons to improve the final aesthetic appearance of the reconstructed breast. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.